A reliable and economically feasible remote sensing system for temperature and relative humidity measurement - Moghavvemi, M.; Ng, K.E.; Soo, C.Y.; Tan, S.Y. (Elsevier, 2005)
Sensing and recording of relative humidity and temperature plays an important role in many industries. In the past analogue devices were used for measurement of relative humidity and temperature. A simple technique combining analogue and digital circuit theory together with programming techniques has been used in this paper to design a remote temperature and relative humidity sensing system. The sensors analogue signal is applied to a micro-controller based data logger for storage purposes. The data is then transferred to the computer through standard RS232 serial port using the user interface program. The program also allows the user to input some of the important parameters such as sampling interval as well as starting date and time for the logging operation. A back-up power supply is also included to enable the system to remain functional in the event of a power failure. The proposed system has added advantages compared with existing systems, namely, in its low cost and high memory capabilities and the ability to perform in both real-time as well as off-line.